Concise enantioselective synthesis of (+)-lentiginosine - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2009)
A high yielding enantioselective synthesis of the indolizidine alkaloid, (+)-lentiginosine, has been described based on asymmetric oza-Cope rearrangement and the L-proline catalyzed alpha-aminooxylation of aldehydes. The strategy also makes use of ring-closing metathesis for the construction of piperidine core. (C) 2009 Elsevier Ltd. All rights reserved.

Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins

Novel synthesis and characterization of titanium superoxide and its application in organic oxidative processes - Reddy, R. Santhosh; Shaikh, Tanveer Mahamadali; Rawat, Varun; Karabal, Pratibha U.; Dewkar, Gajanan; Suryavanshi, Gurunath; Sudalai, Arumugam (Catalysis Surveys from Asia, 2010)
A novel, exceptionally stable titanium superoxide radical ion was prepared and its structure determined by FTIR, ESR, Raman spectroscopy, X-ray diffraction, thermogravimetric/differential thermal analysis and elemental analysis. This heterogeneous catalyst has been found to be effective for the selective oxidation of aromatic amines and phenols to the corresponding nitro aromatics and p-quinones, respectively. In addition, this non-toxic, inexpensive and reusable catalyst has also been used in aminobromination of olefins, which proceed to give the 1, 2-bromoaminated anti-Markovnikov product. A brief account of these results is summarized in this review.
Keywords: Amino Bromination; Anti-Markovnikov; heterogeneous catalyst; Oxidation; Titanium superoxide